ANALISIS PENGARUH LATIHAN FISIK TERHADAP KETERAMPILAN BERMAIN SEPAK BOLA MAHASISWA PENJASKESREK UNIVERSITAS ABULYATAMA - Kurniawan, Erizal; Juwanda, Rawi; Musran, Musran; Syahrianursaifi, Syahrianursaifi; Ilham, Muhammad (Jurnal Dedikasi Pendidikan, 2025)
This study aims to examine the impact of physical training on the skills of playing soccer Penjaskesrek students, Abulyatama University. The study used a quantitative approach, and an experimental method with a one-group pretest-posttest design. Population and research samples of students undergoing physical exercise programs as many as 22 people. Data collection is done by measuring the skills of playing soccer before (pretest) and after (posttest) given treatment in the form of physical exercise. The results of hypothesis analysis using SPSS; Paired Sample T-Test shows that there is a significant difference between pretest and posttest values. The statistical test results obtained a sig (2-tailed) value = 0.000, which is smaller than the significance level α = 0.05 (0.000 ≤ 0.05), so H₀ is rejected and Hₐ is accepted. This finding indicates that physical training significantly contributes to the improvement of students' soccer playing skills. The conclusion of this study is that systematic and directed physical training can improve students' performance in playing soccer. The results of this study are expected to be the basis for designing a more effective training program to support the improvement of football playing skills of Penjaskesrek students at Abulyatama University.